A rare presentation of a common entity: Chronic appendicitis in a patient with back pain - Ekene Onwuka; Joseph Drews; Vinay Prasad; Benedict Nwomeh (Elsevier, 2017)
Despite being one of the most common pediatric surgical diseases, some cases of appendicitis are far from straightforward to diagnose. We present here an interesting case of chronic, retrocecal appendicitis in a dancer who presented with isolated back pain.